An Assessment of Anticancer Activity (MCF-7) and Free Radicals Scavenging Potential of Ferula Asafoetida Synthesized AgNPs through In Vitro Analyses. (10th October 2022) - Thanh, Nguyen Chi; Chinnathambi, Arunachalam; Alahmadi, Tahani Awad; Joshi, Deepika; Jhanani, G. K.; Haile, Adisu
Abstract : Nanomaterials are increasingly being used in pharmaceutical industry to treat a variety of disorders and diseases. Hence, the aim of this research was to evaluate their antioxidant and anticancer activity of presynthesized and characterized plant-based AgNPs against ferric, DPPH, H2 O2, and ABTS free radicals and MCF-7 cell line. Interestingly, the antioxidants assay results revealed that the increased concentration (100 μ g mL -1 ) of AgNPs has remarkable antioxidant ability on ferric (78.20%), DPPH (89.61%), H2 O2 (82.34%), and ABTS (67.95%) free radicals. These scavenging activities were almost close to the free radicals scavenging ability of vitamin C (ascorbic acid). Similarly, test AgNPs showed considerable cytotoxicity (83.15%) against MCF-7 cell line, and it was partially comparable with the cytotoxicity activity (91.35%) of positive control (Doxorubicin). These findings indicate that plant-mediated AgNPs have significant antioxidant and anticancer activity, and thus may be considered for biomedical applications pending the results of some in vivo experiments.